High adsorption efficiency composite carbon-embedded cloth with hot melt type water-absorbing glue net and preparation method thereof
Patent Information
- Application Number
- CN202611073501.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]但现有的夹炭布在实际应用中存在两大无法规避的技术缺陷:
(1)本发明的热熔型吸水胶网层由SAP树脂与热熔粘结树脂、ES纤维及气相二氧化硅交联形成,兼具高倍率吸水锁水、透气不透水、热压自粘结三重功能,将其用在夹炭布中可同步实现定向吸水隔湿、热压自固定活性炭、不封堵微孔、层间牢固复合四大核心功能,从根源上解决水汽竞争吸附问题,同时省去额外喷胶工序,最大化保留活性炭吸附活性,提升夹炭布净化效率、结构稳定性与使用寿命;
Smart Images

Figure CN122976126A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of filter materials technology, and in particular to a high-adsorption-efficiency composite carbon-insulated cloth with a hot-melt absorbent mesh and its preparation method. Background Technology
[0002] Activated carbon cloth, with its well-developed microporous structure and ultra-large specific surface area, is widely used in household air purifiers, vehicle air purification filters, air conditioning filter modules, industrial waste gas deodorization, and kitchen and bathroom odor purification. It can efficiently adsorb harmful air pollutants and odor gases such as formaldehyde, benzene compounds, ammonia, hydrogen sulfide, and volatile organic pollutants.
[0003] Existing conventional carbon-reinforced fabrics mostly use upper and lower non-woven fabric layers combined with activated carbon particles, and are hot-pressed and formed by spraying hot melt adhesive or sprinkling adhesive powder. For example, a carbon-reinforced fabric composite material disclosed in patent CN112389050A includes upper and lower non-woven fabric surface layers, and between the upper and lower non-woven fabric surface layers are arranged a first fiber filament layer, a first activated carbon particle layer, a second fiber filament layer, a bicomponent composite fiber filament layer, a third fiber filament layer, a second activated carbon particle layer, and a fourth fiber filament layer. When using a hot roller mill for pressing, the activated carbon particles are first preheated to 150~160℃ before being spread; the temperature of the heating roller and the pressing roller must reach the melting temperature of the outer layer of the bicomponent composite fiber filament and the fiber filament layer.
[0004] However, existing carbon fiber reinforced cloths have two major unavoidable technical defects in practical applications: First, the problem of water vapor competitive adsorption is prominent in high humidity environments. Water molecules are highly polar and have small molecular dynamic diameters, allowing them to preferentially enter the micropores of activated carbon and occupy effective adsorption sites. This leads to strong competitive adsorption with odor molecules, directly clogging the pore channels of activated carbon. Consequently, the adsorption capacity and rate of activated carbon for odor gases decrease significantly, and the purification efficiency is severely reduced in humid environments. At the same time, once activated carbon is saturated with water, it is prone to clumping, breeding microorganisms, and producing secondary odors such as sour smells, significantly shortening the product's lifespan.
[0005] Secondly, traditional bonding processes have inherent drawbacks. Conventional carbon fiber reinforced cloth requires additional spraying of glue or sprinkling of hot melt adhesive powder to fix the activated carbon. The glue can easily coat the activated carbon particles over a large area and block the micropores, further reducing the adsorption performance. Uneven distribution of the adhesive layer can easily lead to carbon shedding, powder shedding, and interlayer delamination. In addition, the additional glue application process is complex and has high production costs. Furthermore, there is a risk of releasing trace amounts of harmful substances when the adhesive is heated.
[0006] Current technologies mainly focus on improving the iodine value of activated carbon and optimizing the particle size of carbon to improve the adsorption effect. However, they have not simultaneously solved the two core problems of competitive adsorption of water vapor and the adhesion and blockage of micropores by activated carbon. Therefore, they cannot achieve long-term, efficient and stable odor purification in high humidity environments and cannot meet the performance requirements of high-end purification consumables. Summary of the Invention
[0007] This invention aims to overcome the aforementioned problems in the prior art by providing a high-adsorption-efficiency composite carbon-coated cloth with a hot-melt self-adhesive mesh and its preparation method. By employing a hot-melt self-adhesive mesh, it simultaneously achieves four core functions: directional water absorption and moisture isolation, hot-pressing self-fixation of activated carbon, non-clogging of micropores, and strong interlayer bonding. This fundamentally solves the problem of water vapor competitive adsorption, while eliminating the need for an additional adhesive spraying process, maximizing the retention of activated carbon adsorption activity, and improving the purification efficiency, structural stability, and service life of the carbon-coated cloth.
[0008] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a high-adsorption-efficiency composite carbon cloth with a hot-melt absorbent mesh, which adopts a five-layer integrated hot-pressed composite structure; the middle layer is an activated carbon filling layer, and hot-melt absorbent mesh layers are provided on both sides of the activated carbon filling layer; a polyester non-woven fabric layer is provided on the outer layer of the hot-melt absorbent mesh layer. The hot-melt absorbent mesh layer is a cross-linked product of SAP resin, hot-melt adhesive resin, ES fiber and fumed silica.
[0009] This invention utilizes the cross-linking of SAP resin with hot-melt adhesive resin, ES fiber, and fumed silica to form a hot-melt absorbent mesh layer that combines high water absorption and retention, air permeability without water permeability, and hot-press self-adhesion. At room temperature, it is a rigid mesh structure that softens and melts upon heating to generate adhesive force, and solidifies upon cooling. It boasts a water absorption rate of 300-800 times its own weight, a water retention rate ≥90%, and exhibits no swelling, water overflow, or blockage of airflow channels. When used in carbon fiber reinforced cloth, it simultaneously achieves four core functions: directional water absorption and moisture isolation, hot-press self-fixation of activated carbon, non-clogging of micropores, and strong interlayer bonding. This fundamentally solves the problem of water vapor competition for adsorption, while eliminating the need for additional adhesive spraying, maximizing the retention of activated carbon adsorption activity, and improving the purification efficiency, structural stability, and service life of the carbon fiber reinforced cloth.
[0010] In the hot-melt absorbent web of this invention, ES fibers and hot-melt bonding resin can form bonding bridges between SAP resin particles after being added and melted. The resulting hot-melt absorbent web, after cooling and curing, possesses both high strength and porosity. The addition of fumed silica can prevent SAP powder agglomeration, prevent moisture absorption and clumping, improve powder flow, and prevent delamination, thereby enhancing the uniformity of the resulting hot-melt absorbent web.
[0011] Preferably, in the hot-melt absorbent mesh layer, the mass ratio of SAP resin, hot-melt adhesive resin, ES fiber and fumed silica is 35~47:20~35:10~25:0.5~3.
[0012] Preferably, the ES fiber is a core-sheath type thermoplastic adhesive fiber, with the sheath material being PE and the core material being PP. The ES fiber of this invention uses a PE / PP two-component core-sheath type thermoplastic adhesive fiber. After the PE sheath melts, it forms adhesive bridges between SAP resin particles together with the thermoplastic adhesive resin. The PP core layer can maintain the original shape of the fiber, thereby increasing the porosity of the resulting thermoplastic absorbent web layer.
[0013] Preferably, the basis weight of the polyester nonwoven fabric layer is 40~80 g / m². 2 .
[0014] Preferably, the basis weight of the composite layer of polyester nonwoven fabric and hot-melt absorbent web layer is 80~120 g / m². 2 .
[0015] Preferably, the activated carbon filling layer uses coconut shell activated carbon particles with an iodine value ≥1000mg / g and a CTC value ≥60%, with a particle size of 20~100 mesh; the carbon spreading amount is 150±20g / m². 2 .
[0016] Secondly, the present invention provides a method for preparing a high-adsorption-efficiency composite carbon-lined cloth with a hot-melt absorbent mesh, comprising the following steps: (1) Atomize and spray crosslinking agent onto the surface of SAP resin under stirring to coat the surface of SAP resin; then add hot melt adhesive resin, ES fiber and fumed silica in sequence and mix evenly to obtain a mixture. (2) The mixture is evenly spread on a polyester nonwoven fabric substrate, hot-pressed and cross-linked, and then cured at a constant temperature to obtain a composite material. (3) Activated carbon is evenly spread on the composite material, and then another layer of composite material is spread on the activated carbon. The high adsorption efficiency composite carbon cloth is obtained by hot pressing and bonding.
[0017] Preferably, the mass of the crosslinking agent sprayed in step (1) is 0.1 to 2% of the mass of the SAP resin.
[0018] Preferably, the temperature during hot pressing in step (2) is 125~145℃, the pressure is 4~8MPa, and the holding time is 30~60s.
[0019] Preferably, the temperature for constant temperature curing in step (2) is 75~87℃ and the time is 1.5~2h.
[0020] Preferably, the temperature during hot pressing in step (3) is 100~120℃, the pressure is 0.4~0.6MPa, and the hot pressing time is 10~15s.
[0021] Therefore, the present invention has the following beneficial effects: (1) The hot-melt absorbent mesh layer of the present invention is formed by cross-linking SAP resin with hot-melt adhesive resin, ES fiber and fumed silica. It has three functions: high water absorption and water retention, air permeability and water impermeability, and hot-press self-adhesion. When used in carbon-reinforced cloth, it can simultaneously achieve four core functions: directional water absorption and moisture isolation, hot-press self-fixation of activated carbon, non-blocking of micropores, and strong interlayer composite. It solves the problem of water vapor competitive adsorption from the root, and at the same time eliminates the need for additional glue spraying process, maximizes the retention of activated carbon adsorption activity, and improves the purification efficiency, structural stability and service life of carbon-reinforced cloth. (2) In the hot melt absorbent mesh layer of the present invention, SAP resin particles are bonded together by ES fibers and hot melt adhesive resin, and the resulting hot melt absorbent mesh layer can simultaneously have high strength and porosity. Attached Figure Description
[0022] Figure 1 This is a SEM image of the activated carbon filling layer in Example 1 of the present invention.
[0023] Figure 2 This is a SEM image of the activated carbon filling layer in Comparative Example 1 of the present invention.
[0024] Figure 3 This is a comparison chart of toluene removal rates in Examples 1, 1, 3, and 4 of the present invention.
[0025] Figure 4 This is a comparison chart of formaldehyde removal rates between Example 2 and Comparative Example 2 of the present invention. Detailed Implementation
[0026] The present invention will now be further described with reference to the accompanying drawings and specific embodiments.
[0027] In this invention, unless otherwise specified, all equipment and raw materials are available from the market or commonly used in the industry. Unless otherwise specified, the methods in the following embodiments are conventional methods in the art.
[0028] General Implementation Examples: A method for preparing a high-adsorption-efficiency composite carbon-lined cloth with a hot-melt absorbent mesh includes the following steps: (1) Atomize and spray crosslinking agent onto the surface of SAP resin under stirring to coat the surface of SAP resin; then add hot melt adhesive resin, ES fiber and fumed silica in sequence and mix evenly to obtain a mixture. (2) The mixture is evenly spread on a polyester nonwoven fabric substrate, hot-pressed and cross-linked, and then cured at a constant temperature to obtain a composite material. (3) Activated carbon is evenly spread on the composite material, and then another layer of composite material is spread on the activated carbon. The high adsorption efficiency composite carbon cloth is obtained by hot pressing and bonding.
[0029] In one specific implementation, the mass ratio of SAP resin, hot melt adhesive resin, ES fiber and fumed silica in step (1) is 35~47:20~35:10~25:0.5~3.
[0030] In one specific implementation, the mass of the crosslinking agent sprayed in step (1) is 0.1 to 2% of the mass of the SAP resin.
[0031] In one specific implementation, the crosslinking agent mentioned in step (1) is a polyol crosslinking agent.
[0032] In one specific embodiment, the particle size of the SAP resin is 80~120 mesh.
[0033] In one specific embodiment, the ES fiber is a core-sheath type thermoplastic adhesive fiber, with the sheath material being PE and the core material being PP. The ES fiber of this invention uses a PE / PP two-component core-sheath type thermoplastic adhesive fiber. After the PE sheath melts, it forms adhesive bridges between SAP resin particles together with the thermoplastic adhesive resin. The PP core layer can maintain the original fiber shape, thereby increasing the porosity of the resulting thermoplastic absorbent web layer.
[0034] In one specific implementation, the temperature during hot pressing in step (2) is 125~145℃, the pressure is 4~8MPa, and the heat and pressure holding time is 30~60s.
[0035] In one specific implementation, the temperature for constant temperature curing in step (2) is 75~87℃ and the time is 1.5~2h.
[0036] In one specific implementation, the temperature during hot pressing in step (3) is 100~120℃, the pressure is 0.4~0.6MPa, and the hot pressing time is 10~15s.
[0037] In one specific implementation, the basis weight of the polyester nonwoven fabric layer is 40~80 g / m². 2 .
[0038] In one specific implementation, the basis weight of the composite layer of polyester nonwoven fabric and hot-melt absorbent web is 80~120 g / m². 2 .
[0039] In one specific implementation, the activated carbon filling layer uses coconut shell activated carbon particles with an iodine value ≥1000mg / g and a CTC value ≥60%, with a particle size of 20~100 mesh; the carbon spreading amount is 150±20g / m². 2 .
[0040] Example 1:
[0041] A method for preparing a high-adsorption-efficiency composite carbon-reinforced cloth with a hot-melt absorbent mesh, comprising the following steps: (1) Pass the SAP resin through an 80~120 mesh sieve and dry it at 105℃ for 2 hours to remove surface free moisture and prevent hot pressing and bubbling; break up the ES fiber (PE / PP bicomponent core-sheath type hot melt adhesive fiber) to avoid clumping; (2) Add SAP resin to a high-speed mixer and stir at a low speed of 200 r / min. While stirring, spray polyether polyol crosslinking agent onto the surface of SAP resin by atomization to coat the surface of SAP resin. The mass of the sprayed crosslinking agent is 0.5% of the mass of SAP resin. Then, add PES copolyester hot melt adhesive powder, ES fiber and fumed silica in sequence. The mass ratio of SAP resin, PES copolyester hot melt adhesive powder, ES fiber and fumed silica is 45:34:20:1. Mix at 90℃ and 600 r / min for 5 min to obtain the mixture. (3) Spread the mixture evenly on the polyester nonwoven fabric substrate (60 g / m²). 2 Control the thickness of the material to 1.0mm, scrape it flat, and form a uniformly mixed blank; (4) The blank obtained in step (3) is subjected to hot pressing and hot-melt crosslinking; the process parameters are: Hot pressing temperature: 135℃; Hot pressing pressure: 5MPa; Insulation and pressure holding time: 45s; (5) After hot pressing and demolding, the product is placed in an 80℃ oven for 2 hours to further improve cross-linking and eliminate internal stress, resulting in a product with a three-dimensional porous network structure and a basis weight of 100 g / m². 2 Composite materials; (6) Activated carbon is evenly spread on the composite material, and the amount of carbon spread is controlled at 150±20g / m². 2 The activated carbon is 30-60 mesh coconut shell charcoal, CTC-100%, with an iodine value ≥1400 mg / g; then a layer of composite material is laid on the activated carbon, and hot-pressed together to obtain the high adsorption efficiency composite carbon-insulated cloth; the hot-pressing process parameters are: Hot pressing temperature: 110℃; Pressure: 0.5 MPa; Hot pressing time: 12 seconds.
[0042] Example 2:
[0043] A method for preparing a high-adsorption-efficiency composite carbon-reinforced cloth with a hot-melt absorbent mesh, comprising the following steps: (1) Pass the SAP resin through an 80~120 mesh sieve and dry it at 105℃ for 2 hours to remove surface free moisture and prevent hot pressing and bubbling; break up the ES fiber (PE / PP bicomponent core-sheath type hot melt adhesive fiber) to avoid clumping; (2) Add SAP resin to a high-speed mixer and stir at a low speed of 200 r / min. While stirring, spray polyether polyol crosslinking agent onto the surface of SAP resin by atomization to coat the surface of SAP resin. The mass of the sprayed crosslinking agent is 0.5% of the mass of SAP resin. Then, add PES copolyester hot melt adhesive powder, ES fiber and fumed silica in sequence. The mass ratio of SAP resin, PES copolyester hot melt adhesive powder, ES fiber and fumed silica is 45:34:20:1. Mix at 90℃ and 600 r / min for 5 min to obtain the mixture. (3) Spread the mixture evenly on the polyester nonwoven fabric substrate (60 g / m²). 2 Control the thickness of the material to 1.0mm, scrape it flat, and form a uniformly mixed blank; (4) The blank obtained in step (3) is subjected to hot pressing and hot-melt crosslinking; the process parameters are: Hot pressing temperature: 135℃; Hot pressing pressure: 5MPa; Insulation and pressure holding time: 45s; (5) After hot pressing and demolding, the product is placed in an 80℃ oven for 2 hours to further improve cross-linking and eliminate internal stress, resulting in a product with a three-dimensional porous network structure and a basis weight of 100 g / m². 2 Composite materials; (6) Activated carbon is evenly spread on the composite material, and the amount of carbon spread is controlled at 150±20g / m². 2 The activated carbon is a commercially available formaldehyde-modified carbon with a mesh size of 30-60, CTC-100%, and an iodine value ≥1400mg / g. A layer of composite material is then laid on top of the activated carbon and hot-pressed together to obtain the high-adsorption-efficiency composite carbon-lined cloth. The hot-pressing process parameters are as follows: Hot pressing temperature: 110℃; Pressure: 0.5 MPa; Hot pressing time: 12 seconds.
[0044] Comparative Example 1: A method for preparing composite carbon fiber reinforced cloth, comprising the following steps: (1) Spread the PES copolyester hot melt adhesive powder evenly on the polyester nonwoven fabric substrate (60 g / m²). 2 Control the material thickness to 1.0mm, scrape it flat, and form a uniform blank; (2) The ratio of mixed activated carbon and hot melt adhesive resin is 8:1; the activated carbon is 30-60 mesh coconut shell carbon, CTC-100%, iodine value ≥1400mg / g; (3) Spread the mixture from step (2) evenly onto the blank from step (1), controlling the amount to be 168±20g / m 2 The activated carbon content is 150±20 g / m³. 2 Then, polyester nonwoven fabric is laid on the activated carbon and hot-pressed together to obtain the high-adsorption-efficiency composite carbon-insulated cloth; the hot-pressing process parameters are as follows: Hot pressing temperature: 110℃; Pressure: 0.5 MPa; Hot pressing time: 12 seconds.
[0045] Comparative Example 2: A method for preparing composite carbon fiber reinforced cloth, comprising the following steps: (1) Spread the PES copolyester hot melt adhesive powder evenly on the polyester nonwoven fabric substrate (60 g / m²). 2 Control the material thickness to 1.0mm, scrape it flat, and form a uniform blank; (2) Mix activated carbon and hot melt adhesive resin in a ratio of 8:1; the activated carbon is commercially available formaldehyde-removing modified carbon with a mesh size of 30-60, CTC-100%, and an iodine value ≥1400mg / g. (3) Spread the mixture from step (2) evenly onto the blank from step (1), controlling the amount to be 168±20g / m 2 The activated carbon content is 150±20 g / m³. 2 Then, polyester nonwoven fabric is laid on the activated carbon and hot-pressed together to obtain the high-adsorption-efficiency composite carbon-insulated cloth; the hot-pressing process parameters are as follows: Hot pressing temperature: 110℃; Pressure: 0.5 MPa; Hot pressing time: 12 seconds.
[0046] Comparative Example 3 (no ES fibers added to the hot melt absorbent web layer): A method for preparing a high-adsorption-efficiency composite carbon-reinforced cloth with a hot-melt absorbent mesh, comprising the following steps: (1) Pass the SAP resin through an 80~120 mesh sieve and dry it at 105℃ for 2 hours to remove surface free moisture and prevent hot pressing and bubbling. (2) Add SAP resin to a high-speed mixer and stir at a low speed of 200 r / min. While stirring, spray polyether polyol crosslinking agent onto the surface of SAP resin by atomization to coat the surface of SAP resin. The mass of the sprayed crosslinking agent is 0.5% of the mass of SAP resin. Then, add PES copolyester hot melt adhesive powder and fumed silica in sequence. The mass ratio of SAP resin, PES copolyester hot melt adhesive powder and fumed silica is 45:34:1. Mix at 90℃ and 600 r / min for 5 min to obtain the mixture. (3) Spread the mixture evenly on the polyester nonwoven fabric substrate (60 g / m²). 2 Control the thickness of the material to 1.0mm, scrape it flat, and form a uniformly mixed blank; (4) The blank obtained in step (3) is subjected to hot pressing and hot-melt crosslinking; the process parameters are: Hot pressing temperature: 135℃; Hot pressing pressure: 5MPa; Insulation and pressure holding time: 45s; (5) After hot pressing and demolding, the product is placed in an 80℃ oven for 2 hours to further improve cross-linking and eliminate internal stress, resulting in a product with a three-dimensional porous network structure and a basis weight of 100 g / m². 2 Composite materials; (6) Activated carbon is evenly spread on the composite material, and the amount of carbon spread is controlled at 150±20g / m². 2 The activated carbon is 30-60 mesh coconut shell charcoal, CTC-100%, with an iodine value ≥1400 mg / g; then a layer of composite material is laid on the activated carbon, and hot-pressed together to obtain the high adsorption efficiency composite carbon-insulated cloth; the hot-pressing process parameters are: Hot pressing temperature: 110℃; Pressure: 0.5 MPa; Hot pressing time: 12 seconds.
[0047] Comparative Example 4 (No hot melt adhesive resin added to the hot melt absorbent mesh layer): A method for preparing a high-adsorption-efficiency composite carbon-reinforced cloth with a hot-melt absorbent mesh, comprising the following steps: (1) Pass the SAP resin through an 80~120 mesh sieve and dry it at 105℃ for 2 hours to remove surface free moisture and prevent hot pressing and bubbling; break up the ES fiber (PE / PP bicomponent core-sheath type hot melt adhesive fiber) to avoid clumping; (2) Add SAP resin to a high-speed mixer and stir at a low speed of 200 r / min. While stirring, spray polyether polyol crosslinking agent onto the surface of SAP resin by atomization to coat the surface of SAP resin. The mass of the sprayed crosslinking agent is 0.5% of the mass of SAP resin. Then add ES fiber and fumed silica in sequence. The mass ratio of SAP resin, ES fiber and fumed silica is 45:20:1. Mix at 90℃ and 600 r / min for 5 min to obtain the mixture. (3) Spread the mixture evenly on the polyester nonwoven fabric substrate (60 g / m²). 2 Control the thickness of the material to 1.0mm, scrape it flat, and form a uniformly mixed blank; (4) The blank obtained in step (3) is subjected to hot pressing and hot-melt crosslinking; the process parameters are: Hot pressing temperature: 135℃; Hot pressing pressure: 5MPa; Insulation and pressure holding time: 45s; (5) After hot pressing and demolding, the product is placed in an 80℃ oven for 2 hours to further improve cross-linking and eliminate internal stress, resulting in a product with a three-dimensional porous network structure and a basis weight of 100 g / m². 2 Composite materials; (6) Activated carbon is evenly spread on the composite material, and the amount of carbon spread is controlled at 150±20g / m². 2 The activated carbon is 30-60 mesh coconut shell charcoal, CTC-100%, with an iodine value ≥1400 mg / g; then a layer of composite material is laid on the activated carbon, and hot-pressed together to obtain the high adsorption efficiency composite carbon-insulated cloth; the hot-pressing process parameters are: Hot pressing temperature: 110℃; Pressure: 0.5 MPa; Hot pressing time: 12 seconds.
[0048] SEM images of the activated carbon filling layers in Example 1 and the comparative example are shown below. Figure 1 and Figure 2 As shown in the figure, in Example 1, the hot-melt absorbent mesh layer of the present invention is used for hot-melt bonding, and there is no adhesive powder between the activated carbon particles, which does not affect the gas adsorption performance. However, in Comparative Example 1, hot-melt bonding resin is used for hot-melt bonding, and there is adhesive powder between the activated carbon particles, which will affect its gas adsorption performance.
[0049] The removal efficiency of the composite carbon-reinforced cloth obtained in Example 1 and Comparative Examples 1, 3, and 4 for toluene removal was tested. The method was as follows: the carbon-reinforced cloth was cut into circular pieces with a diameter of 17 mm and placed in the middle of a reaction tube; a toluene standard gas with a concentration of 15 ppm was introduced into the reaction tube, and the concentration difference between the upstream and downstream sides of the reaction tube was measured to calculate the removal efficiency of toluene on the carbon-reinforced cloth; the inner diameter of the reaction tube was 17 mm, and the gas flow rate was 2.0 L / min; the testing instrument was a RAE PGM-7340 VOC detector from the USA. The results are as follows: Figure 3 As shown in the image.
[0050] from Figure 3 As can be seen from the data, in Example 1, the use of the hot-melt absorbent mesh layer of the present invention for hot-melt composite bonding can simultaneously achieve directional water absorption and moisture isolation, hot-pressing self-fixation of activated carbon, non-clogging of micropores, and strong interlayer bonding. The resulting carbon-reinforced cloth has a high toluene removal rate, and can maintain a high removal rate even after continuous use. In contrast, in Comparative Example 1, hot-melt adhesive resin was directly used for composite bonding without the hot-melt absorbent mesh layer of the present invention. The adhesive powder would clog the activated carbon pores, and water molecules would compete with toluene for adsorption, resulting in a significant decrease in the adsorption effect of the carbon-reinforced cloth on toluene compared with Example 1. In Comparative Example 3, no ES fiber was added to the hot-melt absorbent mesh layer, and only hot-melt adhesive resin was used to bond the SAP particles. The porosity of the hot-melt absorbent mesh layer decreased, the water absorption rate slowed down, and it could not effectively avoid the competitive adsorption of water vapor. The adsorption effect on toluene was also lower than that of Example 1. In Comparative Example 4, when no hot-melt adhesive resin was added to the hot-melt absorbent mesh layer and only ES fiber was used to bond the SAP particles, the bonding effect was weak. Although the toluene removal performance improved to some extent, the carbon-coated cloth layers separated from each other, resulting in severe carbon leakage, making it impossible to mass-produce filters.
[0051] The formaldehyde removal efficiency of the carbon-reinforced cloths obtained in Example 2 and Comparative Example 2 was tested using a formaldehyde standard gas with a concentration of 1 ppm and a formaldehyde detector. The results are as follows: Figure 4 As shown. From Figure 4 As can be seen, in Comparative Example 2, the adsorption effect of formaldehyde by directly using hot melt adhesive resin for composite is significantly reduced compared with that in Example 2.
[0052] It should be noted that the specific implementation methods described above provide a detailed explanation of the technical solution and application results of the present invention. The above embodiments are only the most preferred embodiments and are not intended to limit the present invention. Modifications or equivalent substitutions made by those skilled in the art within the core theoretical scope of the present invention should all fall within the protection scope of the present invention.
Claims
1. A high-adsorption-efficiency composite carbon-lined cloth with a hot-melt absorbent mesh, characterized in that, It adopts a five-layer integrated hot-pressed composite structure; the middle layer is an activated carbon filling layer, and hot-melt water-absorbing adhesive mesh layers are provided on both sides of the activated carbon filling layer; the outer layer of the hot-melt water-absorbing adhesive mesh layer is a polyester non-woven fabric layer; The hot-melt absorbent mesh layer is a cross-linked product of SAP resin, hot-melt adhesive resin, ES fiber and fumed silica.
2. The high-adsorption-efficiency composite carbon-lined cloth with a hot-melt absorbent mesh according to claim 1, characterized in that, In the hot-melt absorbent mesh layer, the mass ratio of SAP resin, hot-melt adhesive resin, ES fiber and fumed silica is 35~47:20~35:10~25:0.5~3.
3. The high-adsorption-efficiency composite carbon-lined cloth with a hot-melt absorbent mesh according to claim 1 or 2, characterized in that, The ES fiber is a core-sheath type thermoplastic adhesive fiber, with PE as the sheath material and PP as the core material.
4. The high-adsorption-efficiency composite carbon-lined cloth with a hot-melt absorbent mesh according to claim 1, characterized in that, The basis weight of the polyester nonwoven fabric layer is 40~80g / m². 2 .
5. The high-adsorption-efficiency composite carbon-lined cloth with a hot-melt absorbent mesh according to claim 1 or 4, characterized in that, The weight of the composite layer of polyester nonwoven fabric and hot-melt absorbent web is 80~120 g / m². 2 .
6. The high-adsorption-efficiency composite carbon-lined cloth with a hot-melt absorbent mesh according to claim 1, characterized in that, The activated carbon filling layer uses coconut shell activated carbon particles with an iodine value ≥1000mg / g and a CTC value ≥60%, with a particle size of 20~100 mesh; the carbon spreading amount is 150±20g / m². 2 .
7. A method for preparing a high-adsorption-efficiency composite carbon-lined cloth with a hot-melt absorbent mesh as described in any one of claims 1 to 6, characterized in that, Includes the following steps: (1) Atomize and spray crosslinking agent onto the surface of SAP resin under stirring to coat the surface of SAP resin; then add hot melt adhesive resin, ES fiber and fumed silica, and mix evenly to obtain a mixture. (2) The mixture is evenly spread on a polyester nonwoven fabric substrate, hot-pressed and cross-linked, and then cured at a constant temperature to obtain a composite material. (3) Activated carbon is evenly spread on the composite material, and then another layer of composite material is spread on the activated carbon. The high adsorption efficiency composite carbon cloth is obtained by hot pressing and bonding.
8. The method for preparing the high-adsorption-efficiency composite carbon-lined cloth with a hot-melt absorbent mesh according to claim 7, characterized in that, The mass of the crosslinking agent sprayed in step (1) is 0.1 to 2% of the mass of the SAP resin.
9. The method for preparing the high-adsorption-efficiency composite carbon-lined cloth with a hot-melt absorbent mesh according to claim 7, characterized in that, In step (2), the temperature during hot pressing is 125~145℃, the pressure is 4~8MPa, and the holding time is 30~60s; the temperature for constant temperature curing is 75~87℃, and the time is 1.5~2h.
10. The method for preparing high-adsorption-efficiency composite carbon-lined cloth with a hot-melt absorbent mesh according to claim 7 or 9, characterized in that, In step (3), the temperature during hot pressing is 100~120℃, the pressure is 0.4~0.6MPa, and the hot pressing time is 10~15s.
Citation Information
Patent Citations
Carbon-carrying cloth composite material
CN112389050A
